LINGKUNGAN HIDUP DAN PERILAKU KONSUMTIF DALAM KARYA SENI LUKIS SUREALIS - Govinda Mulya Putra; Erfahmi Erfahmi (Serupa The Journal of Art Education, 2020)
The purpose of this final talk is to visualize the Environment and Consumptive as a Concept  Bringing Senior Artwork. Showing adverse effects on life, self, nature, and the surrounding environment. The methods used in this final work process are: (1) Preparation, (2) Elaboration, (3) Synthesis, (4) Realization of Concepts, (5) Completion. The visualization of this consumptive challenge reveals that people cannot distinguish between needs and desires, so that they can do things that they don't like right away as needed and produce something that ultimately has a negative impact on culture, self, nature, and the environment. The titles of the ten final works are: Faded, Never Enough, Poachers, Unreasonable, Prohibition Servants, Satisfied? Never, Longevity, Explorers and Mothers.Kata Kunci: Lingkungan Hidup dan Perilaku Konsumtif, Seni Lukis, Surealis.